1999
DOI: 10.1046/j.1468-2982.1999.019007660.x
|View full text |Cite
|
Sign up to set email alerts
|

Glyceryl Trinitrate Induces Attacks of Migraine Without Aura in Sufferers of Migraine with Aura

Abstract: Migraine with aura and migraine without aura have the same pain phase, thus indicating that migraine with aura and migraine without aura share a common pathway of nociception. In recent years, increasing evidence has suggested that the messenger molecule nitric oxide (NO) is involved in pain mechanisms of migraine without aura. In order to clarify whether the same is true for migraine with aura, in the present study we examined the headache response to intravenous infusion of glyceryl trinitrate (GTN) (0.5 mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
166
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(179 citation statements)
references
References 31 publications
10
166
3
Order By: Relevance
“…36 However, an attack fulfilling criteria for migraine without aura developed in 6 of 12 patients. 35 This was significantly more than in the normal controls in which no one developed a migraine attack. It was concluded that GTN can not induce an aura, but patients having migraine with aura are more prone to develop a migraine attack without aura than normal controls.…”
Section: Migrainementioning
confidence: 73%
See 1 more Smart Citation
“…36 However, an attack fulfilling criteria for migraine without aura developed in 6 of 12 patients. 35 This was significantly more than in the normal controls in which no one developed a migraine attack. It was concluded that GTN can not induce an aura, but patients having migraine with aura are more prone to develop a migraine attack without aura than normal controls.…”
Section: Migrainementioning
confidence: 73%
“…Twelve sufferers of migraine with aura who never had attacks without aura were therefore compared to 14 healthy subjects. 35 Both groups received GTN (0.5 m/kg/min for 20 min). Aura symptoms were not elicited in any subject, but have subsequently been observed by others in rare instances after GTN.…”
Section: Migrainementioning
confidence: 99%
“…The average number of CGRP-positive neurons in the saline-treated animals was 53 AE 5 per slice, in the GTN-treated animals 93 AE 4 (p ¼ .028; Figure 2A). The increase in CGRP-immunopositive cells after GTN treatment was found both in V1 and in V2/3 (ANOVA F (1,8) ¼ 6.4, p ¼ .035, HSD post-hoc tests both p < .001; Figure 3). The size of CGRP-ir and nNOS-ir neurons was not significantly different between GTN-treated and control animals.…”
Section: Cgrp Immunoreactive Neuronsmentioning
confidence: 89%
“…The average number of nNOS-ir neurons per slice was 3.6 AE 0.8 in the saline-treated animals, and 8.0 AE 0.8 in the GTN-treated group (p ¼ .028, Figure 2B). After infusion of GTN an increase in the number of nNOS positive neurons was observed in the V1 division (ANOVA F (1,8) …”
Section: Nnos Immunoreactive Neuronsmentioning
confidence: 99%
“…One of the main side effects of NTG is migraine, which may develop within minutes, or up to four hours post-administration. 4) Systemic NTG activates nociceptive neurons in areas of the mouse brain. 5) In mice, a single injection of NTG induces acute mechanical, cold, and thermal hypersensitivity, which persists up to four hours post-injection.…”
mentioning
confidence: 99%